Solid electrolyte, preparation method and all-solid-state battery
By using yLi2O2·MXa(OCN)b as the solid electrolyte, combined with the ball milling heat treatment method of lithium hydroxide, metal M halide and cyanate, the existing technology solves the problem of amorphous halide electrolyte having both soft quality and high quality. The issue of ionic conductivity has significantly improved the electrochemical performance of all-solid-state batteries.
Patent Information
- Application Number
- CN202411417700.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to maintain the soft properties of the amorphous halide electrolyte while taking into account the improvement of its ionic conductivity, or to reduce Young's modulus while improving the ionic conductivity, making it difficult to effectively improve the electrochemical performance of the electrolyte.
Use yLi2O2·MXa(OCN)b as the solid electrolyte, where 0.5≤y≤1, 0≤a<4, 0
While maintaining the quality of the quality, it has significantly improved the ionic conductivity of solid electrolytes, reducing the amount of Yang's modulus, improving the electrochemical properties of all -solid -state batteries, and suitable for the performance requirements of a variety of all -solid -state batteries.
Smart Images

Figure BDA0005079895120000041 
Figure BDA0005079895120000131 
Figure HDA0005079895130000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a solid electrolyte, a preparation method and an all-solid-state battery. Background Art
[0002] Amorphous halide solid electrolytes have the characteristics of softness, high conductivity, wider composition variation and isotropic ion conduction. All-solid-state batteries with amorphous halide solid electrolytes have attracted increasing interest from researchers due to their potential high rate, high safety and high specific energy characteristics.
[0003] Moreover, compared with crystalline electrolytes, the ionic conductivity of amorphous halide electrolytes has room for further improvement. On the one hand, the soft and compactible properties of amorphous electrolytes must be maintained. On the other hand, the higher rate performance requirements of batteries put forward higher requirements on the conductivity of electrolytes. In the prior art, the heat treatment temperature of amorphous halide electrolytes is often increased or strongly coordinated Cl is doped. - / Br - However, it is not possible to make the amorphous halide electrolyte maintain its soft properties while taking into account the ionic conductivity, or to maintain the ionic conductivity high enough while reducing the Young's modulus, so it is difficult to effectively improve the ionic conductivity. Summary of the invention
[0004] In order to solve the problems of the prior art, the embodiments of the present invention provide a solid electrolyte, a preparation method and an all-solid-state battery. The technical solution is as follows:
[0005] In one aspect, the present invention provides a solid electrolyte comprising yLi2O2·MX a (OCN) b , wherein 0.5≤y≤1, 0≤a<4, 0<b≤4, a+b=3 or 4, X is at least one of Cl and Br, and M is at least one of Ta, Hf and Nb.
[0006] Further, 0.5≤y≤0.75.
[0007] Furthermore, the crystal structure of the solid electrolyte is at least one of an amorphous state and a microcrystalline state.
[0008] Furthermore, the Young's modulus of the solid electrolyte is less than or equal to a preset Young's modulus, and the preset Young's modulus is 7 Gpa to 10 Gpa;
[0009] The ionic conductivity of the solid electrolyte is greater than or equal to a preset conductivity, and the preset conductivity is 5 mS / cm to 7 mS / cm.
[0010] Furthermore, the solid electrolyte also includes Li3YCl6, Li3InCl6, Li2S·P2S5, Li2S·P2S5·LiI, Li2S·P2S5·LiCl, Li2S·P2S5·LiBr, Li2S·P2S5·Li2O, Li2S·P2S5·Li2O·LiI, Li2S·SiS2, Li2S·SiS2·LiI, Li2S·SiS2·LiBr, Li2S·SiS2·LiCl, Li2S·SiS2·B2S3·LiI, Li2S·SiS2·P2S5·LiI, Li2S·B2S3, Li2S·P2S5·Z m S n , Li2S·GeS2, Li2S·SiS2·Li3PO4, Li2S·SiS2·Li c NO d and Li 10 GeP2S 12 At least one of;
[0011] Wherein, m and n are positive numbers, Z is one of Ge, Zn and Ga; c and d are positive numbers, and N is one of P, Si, Ge, B, Al, Ga and In.
[0012] Furthermore, the solid electrolyte is used in an all-solid-state battery, which includes a positive electrode layer, a negative electrode layer and an isolation layer, wherein the isolation layer is located between the positive electrode layer and the negative electrode layer, and at least one of the positive electrode layer, the negative electrode layer and the isolation layer includes the solid electrolyte.
[0013] On the other hand, the present invention also provides an all-solid-state battery, comprising the solid electrolyte as described in any one of the above items.
[0014] On the other hand, the present invention also provides a method for preparing a solid electrolyte, comprising:
[0015] The solid electrolyte is obtained by mixing lithium hydroxide, a halide of metal M and a cyanate of metal M with a ball mill and performing a heat treatment. The solid electrolyte includes yLi2O2·MX a (OCN) b , wherein 0.5≤y≤1, 0≤a<4, 0<b≤4, a+b=3 or 4, X is at least one of Cl and Br, and M is at least one of Ta, Hf and Nb.
[0016] Furthermore, the heat treatment temperature is 50°C to 80°C, and the time is 0.5h to 3h.
[0017] Furthermore, the lithium hydroxide, the halide of metal M and the cyanate of metal M are mixed and ball-milled, and then heat-treated to obtain the solid electrolyte, which comprises:
[0018] The lithium hydroxide, the halide of the metal M, the cyanate of the metal M and the dispersion medium are mixed and ball-milled to obtain a ball-milled mixture; during the ball-milling process, the lithium hydroxide, the halide of the metal M and the cyanate of the metal M undergo an amorphization reaction to generate a precursor, and the ball-milled mixture includes the precursor and the dispersion medium;
[0019] performing separation treatment on the ball-milled mixture to obtain a separated precursor;
[0020] The separated precursor is heat treated to obtain the solid electrolyte.
[0021] The implementation of the present invention has the following beneficial effects:
[0022] 1. The solid electrolyte of the present invention comprises yLi2O2·MX a (OCN) b , using cyanate with a larger ion radius to replace part of the halogen, breaking through the research bottleneck of the traditional Li2O2·MX binary glass-ceramic system, while maintaining the soft properties of the solid electrolyte, taking into account the improvement of the ionic conductivity of the solid electrolyte, and being able to work stably at high potentials, which can greatly improve the electrochemical performance of the solid electrolyte and the all-solid-state battery with the solid electrolyte; in addition, the solid electrolyte can be applied to a variety of all-solid-state batteries, meeting the performance requirements of different all-solid-state batteries, and has a wide range of applications.
[0023] 2. The solid electrolyte of the present invention is prepared by mixing lithium hydroxide, a halide of metal M and a cyanate of metal M, ball-milling and heating. The raw materials are readily available and inexpensive, and the preparation method is simple and fast, which can save preparation costs and is conducive to large-scale production of solid electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 A schematic diagram of the structure of an all-solid-state battery provided by the present invention;
[0026] Figure 2 A flow chart of a method for preparing a solid electrolyte provided in an embodiment of the present invention;
[0027] Figure 3 A flow chart of another method for preparing a solid electrolyte provided by an embodiment of the present invention;
[0028] Figure 4 is the XRD diffraction pattern of the solid electrolyte in Example 1 of the present invention;
[0029] Figure 5 is the XRD diffraction pattern of the solid electrolyte in Example 7 of the present invention;
[0030] Figure 6 is the XRD diffraction pattern of the solid electrolyte in Example 8 of the present invention;
[0031] Figure 7 is the XRD diffraction pattern of the solid electrolyte in Example 9 of the present invention;
[0032] Figure 8 This is the XRD diffraction pattern of the solid electrolyte in Comparative Example 3 of the present invention.
[0033] Wherein, the accompanying drawings are marked as follows:
[0034] 1- positive electrode layer, 11- positive electrode active material, 12- positive electrode side solid electrolyte, 2- negative electrode layer, 21- negative electrode active material, 22- negative electrode side solid electrolyte. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe specific objects or a sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product, or server that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products, or devices.
[0037] It should be understood that when an element or layer is referred to as "on ...", "adjacent to ...", "connected to" or "coupled to" other elements or layers, it can be directly on, adjacent to, connected to or coupled to other elements or layers, or there can be intervening elements or layers. On the contrary, when an element is referred to as "directly on ...", "directly adjacent to ...", "directly connected to" or "directly coupled to" other elements or layers, there are no intervening elements or layers. It should be understood that the depth direction of an element or layer is the direction perpendicular to the surface of the element or layer, and the direction of the cross section of an element or layer is the direction parallel to the surface direction of the element or layer. It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present invention, the first element, component, region, layer or part discussed below can be represented as the second element, component, region, layer or part. When a second element, component, region, layer or section is discussed, it does not necessarily mean that the first element, component, region, layer or section must be present in the invention.
[0038] In order to solve the problem that the existing halide electrolyte cannot improve the ion conductivity and reduce the Young's modulus at the same time, the embodiment of the present invention provides a solid electrolyte, the solid electrolyte includes yLi2O2·MX a (OCN) b , wherein 0.5≤y≤1, 0≤a<4, 0<b≤4, a+b=3 or 4, X is a halogen, further, X is at least one of Cl and Br, and M is at least one of Ta, Hf and Nb.
[0039] The Lewis structure of cyanate is:
[0040]
[0041] OCN - ) is driven by its unique linear cation-anion coordination chemistry, which gives cyanate special ion transport properties; cyanate is chemically and structurally similar to iodide (I - ) are similar in that they both have large polarizable anions; in addition, OCN - The electrons are mainly concentrated in oxygen ions (O 2- ) so that O 2- Easier to participate in the coordination of other elements.
[0042] In the solid electrolyte, cyanate with a larger ion radius replaces part of the halogen, which is suitable for obtaining a high-temperature fast conduction phase, a high defect concentration and a low activation energy at room temperature through anion and cation doping, so that the solid electrolyte has a higher lithium ion transmission capacity; the OCN - The ionic radius (197 pm) and I - The ionic radius (181 pm) is close to that of I - The ionic radius and surface charge distribution density are lower, making yLi2O2·MX a (OCN) b The effective ion potential ratio of the system increases; and the increase of O 2- Content makes the connection [MXO] - Unit and adjacent [MXO] - The polarizability of the bridging oxygen of the unit increases, the charge is further delocalized, and the linear structure of OCN - The incorporation of short-range lattices can relatively improve the room temperature ionic conductivity of amorphous halide electrolytes; and, compared with LiCl (886K) and LiBr (823K), LiOCN has a lower melting point of 648K and a lower lattice energy, which allows the solid electrolyte to maintain a lower Young's modulus, helping to increase the contact area between the electrode sheet and the solid electrolyte in the all-solid-state battery, thereby improving the rate performance of the all-solid-state battery; in this way, the ionic conductivity of the solid electrolyte can be effectively improved, while the Young's modulus of the solid electrolyte can be reduced, so that the solid electrolyte has both high ionic conductivity and soft properties, and is further beneficial to the improvement of the rate performance of the all-solid-state battery having the solid electrolyte.
[0043] Among them, the solid electrolyte yLi2O2·MX a (OCN) b It belongs to the halide solid electrolyte; further, the solid electrolyte belongs to the Li2O2·MX binary amorphous or microcrystalline halide solid electrolyte system. The crystal structure of the solid electrolyte is short-range ordered and long-range disordered. It is composed of a one-dimensional chain skeleton structure, with a low filling rate of the crystal structure and a large distance between the cation and anion ligands. The distance between the carrier and the anion constituting the skeleton structure is large, which makes the electrostatic interaction between the ion conducting material and the anion small, thereby improving the ion conductivity of the solid electrolyte. From the perspective of electronic structure, increasing O 2- Content makes connections [MXO] - Unit and adjacent [MXO] - The polarizability of the bridging oxygen of the unit increases, which is conducive to further delocalization of the charge, causing the charge density of the negatively charged ligand to decrease, further reducing the lithium ion (Li +In addition, from the perspective of ion potential, when the lithium ion potential is constant, the weighted cation potential is constant, and the weighted anion potential decreases with the increase of ion radius, the effective ion potential ratio can be increased, thereby weakening the interaction between anions and carriers and reducing Li + Diffusion barrier, thereby synergistically improving the ionic conductivity of solid electrolytes from multiple aspects.
[0044] Specifically, in some preferred embodiments, 0.5≤y≤0.75; it can be understood that the value of y can be any point value between 0.5 and 0.75; illustratively, the value of y can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, etc.; in this way, the ionic conductivity of the solid electrolyte can be further improved, and at the same time, it is further beneficial to reduce the Young's modulus, making the solid electrolyte softer. When used in an all-solid-state battery, it can be more closely bonded to the battery materials in the all-solid-state battery, reducing structural defects in the all-solid-state battery, which is beneficial to improving the performance of the solid electrolyte and the all-solid-state battery having the solid electrolyte.
[0045] Specifically, the crystal structure of the solid electrolyte is at least one of an amorphous state and a microcrystalline state, and tends to an amorphous structure as much as possible, which is beneficial to further improve the ionic conductivity of the solid electrolyte and further soften the texture of the solid electrolyte; wherein, the amorphous state may refer to a completely amorphous state, that is, there is no peak in the XRD diffraction spectrum corresponding to the amorphous solid electrolyte, which is a desired ideal state. In the case of the amorphous state, the ionic conductivity is higher and the texture is softer; the microcrystalline state refers to that the crystal structure of the solid electrolyte is mainly amorphous, and there are a large number of structures existing in an amorphous state and extremely small amounts of crystalline particles (i.e., crystals) in the crystal structure, and these extremely small amounts of crystalline particles are dispersed in a large amount of amorphous states; or, the microcrystalline state may also refer to a crystal structure in which the crystal structure of the solid electrolyte is in a transitional state between a completely amorphous state and a crystalline state, and the XRD diffraction spectrum of the microcrystalline solid electrolyte has not yet measured a state of diffraction peaks, but the diffraction peaks have begun to aggregate to form a relatively gentle arc, and there is a trend of forming a diffraction peak, and the solid electrolyte corresponding to this state may also be called a microcrystalline solid electrolyte.
[0046] Specifically, the Young's modulus of the solid electrolyte is less than or equal to a preset Young's modulus, and the preset Young's modulus is 7Gpa~10Gpa; it can be understood that the preset Young's modulus can be any point value between 7Gpa~10Gpa; exemplarily, the preset Young's modulus can be 7Gpa, 7.5Gpa, 7.7Gpa, 8Gpa, 8.4Gpa, 9Gpa, 9.2Gpa, 10Gpa, etc.
[0047] The ionic conductivity of the solid electrolyte is greater than or equal to the preset conductivity, and the preset conductivity is 5mS / cm to 7mS / cm; it can be understood that the preset conductivity can be any point value between 5mS / cm and 7mS / cm; illustratively, the preset conductivity can be 5mS / cm, 5.4mS / cm, 6mS / cm, 6.3mS / cm, 6.8mS / cm, 7mS / cm, etc.
[0048] In this way, the solid electrolyte has not only high ionic conductivity, but also a low Young's modulus and a soft texture. When used in all-solid-state batteries, it can improve the electrochemical performance of the all-solid-state battery through higher ionic conductivity, while improving the bonding tightness and adhesion reliability between the solid electrolyte and other battery materials in the all-solid-state battery through its softer texture, reducing the structural defects of the all-solid-state battery, which is further beneficial to the improvement of the electrochemical performance of the all-solid-state battery.
[0049] Specifically, the solid electrolyte also includes Li3YCl6, Li3InCl6, Li2S·P2S5, Li2S·P2S5·LiI, Li2S·P2S5·LiCl, Li2S·P2S5·LiBr, Li2S·P2S5·Li2O, Li2S·P2S5·Li2O·LiI, Li2S·SiS2, Li2S·SiS2·LiI, Li2S·SiS2·LiBr, Li2S·SiS2·LiCl, Li2S·SiS2·B2S3·LiI, Li2S·SiS2·P2S5·LiI, Li2S·B2S3, Li2S·P2S5·Z m S n , Li2S·GeS2, Li2S·SiS2·Li3PO4, Li2S·SiS2·Li c NO d and Li 10 GeP2S 12 At least one of; wherein m and n are positive numbers, Z is one of Ge, Zn and Ga; c and d are positive numbers, N is one of P, Si, Ge, B, Al, Ga and In; thus, with yLi2O2·MX a (OCN) b Mixing can further improve the overall performance of the solid electrolyte, allowing the solid electrolyte to meet the performance requirements of different all-solid-state batteries, greatly improving the applicability of the solid electrolyte and expanding its scope of application.
[0050] Specifically, the solid electrolyte is used in an all-solid-state battery, which includes a positive electrode layer, a negative electrode layer and a separation layer, wherein the separation layer is located between the positive electrode layer and the negative electrode layer, and at least one of the positive electrode layer, the negative electrode layer and the separation layer includes a solid electrolyte; in some exemplary embodiments, the positive electrode layer, the negative electrode layer or the separation layer includes a solid electrolyte; in other exemplary embodiments, at least two of the positive electrode layer, the negative electrode layer and the separation layer include a solid electrolyte; in other exemplary embodiments, the positive electrode layer, the negative electrode layer and the separation layer all include a solid electrolyte; in this way, the setting position of the solid electrolyte is flexible and changeable, which can meet the performance requirements of different battery materials, thereby meeting the performance improvement requirements of different all-solid-state batteries.
[0051] On the other hand, an embodiment of the present invention further provides an all-solid-state battery, comprising the solid electrolyte as described above, which can effectively improve the ionic conductivity and rate performance of the all-solid-state battery.
[0052] For example, Figure 1 As shown, the all-solid-state battery includes a positive electrode layer 1 and a negative electrode layer 2, wherein the positive electrode layer 1 includes a positive electrode active material 11 and a positive electrode side solid electrolyte 12, and the negative electrode layer 2 includes a negative electrode active material 21 and a negative electrode side solid electrolyte 22, and the positive electrode side solid electrolyte 12 is located between the positive electrode active material 11 and the negative electrode side solid electrolyte 22, and the negative electrode side solid electrolyte 22 is located between the positive electrode side solid electrolyte 12 and the negative electrode active material 21, so that the two layers of solid electrolytes, the positive electrode side solid electrolyte 12 and the negative electrode side solid electrolyte 22, are located as a whole between the positive electrode active material 11 and the negative electrode active material 21, which is beneficial to ion conduction and improves the electrochemical properties of the all-solid-state battery, such as the rate performance.
[0053] Specifically, the all-solid-state battery further includes an isolation layer, which is located between the positive electrode layer and the negative electrode layer and is a solid electrolyte layer; in some preferred embodiments, the solid electrolyte yLi2O2·MX a (OCN) b Located in the positive electrode layer, or solid electrolyte yLi2O2·MX a (OCN) b Located on the side of the isolation layer facing the positive electrode layer, it is beneficial to further improve the ion conductivity and enhance the performance of the all-solid-state battery.
[0054] Specifically, the positive electrode active material in the positive electrode layer includes LiCoO2, LiMnO2, LiNiO2, LiVO2, Li 1+x Ni 1 / 3Co 1 / 3 Mn 1 / 3O2, spinel-type active materials, inverse spinel-type active materials, olivine-type active materials, silicon-containing active materials, rock salt layer-type active materials in which part of the transition metals are replaced by heterogeneous metals, spinel-type active materials in which part of the transition metals are replaced by heterogeneous metals, lithium titanate and at least one of sulfide active materials; the solid electrolyte can be applied to a variety of different positive electrode active materials to improve the electrochemical properties of the positive electrode layer, has a wide range of applications, and can meet the performance improvement requirements of different positive electrode layers.
[0055] For example, the spinel active material may include LiMn2O4 and Li(Ni 0.5 Mn 1.5 )O4; the inverse spinel type active material may include at least one of LiNiVO4 and LiCoVO4; the olivine type active material may include at least one of LiFePO4, LiMnPO4, LiCoPO4 and LiNiPO4; the silicon-containing active material may include at least one of Li2FeSiO4 and Li2MnSiO; the rock salt layer type active material in which part of the transition metal is replaced by a heterogeneous metal may be LiNi 0.8 Co (0.2e) Al e O2, wherein 0<e<0.2; Exemplarily, the spinel active material in which a part of the transition metal is replaced by a heterogeneous metal may be Li 1+f Mn 2fg Y g O4 (wherein Y includes at least one of Al, Mg, Co, Fe, Ni, and Zn, and 0<f+g<2); For example, lithium titanate may be Li4Ti5O 12 Etc.; illustratively, the sulfide active material may include copper sulfide, iron sulfide, cobalt sulfide, nickel sulfide, and the like.
[0056] Specifically, the negative electrode active material in the negative electrode layer includes at least one of a metal material, a carbon material, an oxide, a nitride, a tin compound and a silicon compound; the solid electrolyte can be applied to a variety of different negative electrode active materials to improve the electrochemical properties of the negative electrode layer, has a wide range of applications, and can meet the performance improvement requirements of different negative electrode layers.
[0057] Exemplarily, the metal material can be a metal element or an alloy, for example, lithium metal or a lithium alloy; Exemplarily, the carbon material can be at least one of natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite and amorphous carbon; Exemplarily, the negative electrode active material can also be silicon, tin, a silicon compound or a tin compound, which has a high capacity density and is beneficial to improving the electrochemical properties of the battery material.
[0058] On the other hand, Figure 2As shown, an embodiment of the present invention also provides a method for preparing a solid electrolyte, comprising:
[0059] S1, mixing lithium hydroxide, a halide of metal M and a cyanate of metal M with ball milling, and heat treating to obtain the solid electrolyte; the solid electrolyte includes yLi2O2·MX a (OCN) b , wherein 0.5≤y≤1, 0≤a<4, 0<b≤4, a+b=3 or 4, X is at least one of Cl and Br, and M is at least one of Ta, Hf and Nb.
[0060] Among them, lithium hydroxide (LiOH), a halide of metal M and a cyanate of metal M are mixed to form a mixed raw material, and according to the ratio in the final product, the molar ratio is 0.5y:(a / a+b):(b / a+b); then, in the process of ball milling the mixed raw material, the mixed raw material is mixed with a ball milling medium for ball milling, and lithium hydroxide, a halide of metal M and a cyanate of metal M undergo an amorphization reaction under high-speed ball milling to generate a precursor; then, the ball milling medium is separated to obtain a separated precursor, and the separated precursor is heat-treated to remove residual gaseous HCl and HOCN in the precursor to obtain a solid electrolyte. The steps are simple, the operation is convenient, and the preparation accuracy is good, which is beneficial to improving the ionic conductivity and soft properties of the solid electrolyte.
[0061] Specifically, during the ball milling process, the mass ratio of the mixed raw material to the ball milling medium (i.e., the ball milling balls) is 1:1 to 1:50, the rotation speed is 300 rpm to 500 rpm, and the time is 1 h to 35 h; it can be understood that the mass ratio of the mixed raw material to the ball milling medium can be any value between 1:1 and 1:50, the rotation speed can be any value between 300 rpm to 500 rpm, and the time can be any value between 1 h to 35 h; illustratively, the mass ratio of the mixed raw material to the ball milling medium can be 1:1, 1:5, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190, 1:200, 1:210, 1:220, 1:350, 1:360, 1:400, 1:5 :30, 1:40, 1:50, etc., the rotation speed can be 300rpm, 320rpm, 350rpm, 380rpm, 400rpm, 450rpm, 470rpm, 500rpm, etc., and the time can be 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, etc.; in this way, under high-speed ball milling conditions, the mixed raw materials can be effectively broken up to form an amorphous crystal structure, thereby improving the preparation yield and preparation accuracy of the solid electrolyte, which is beneficial to improving the ionic conductivity and soft properties of the solid electrolyte.
[0062] Specifically, Figure 3 As shown, in some exemplary embodiments, the lithium hydroxide, the halide of metal M and the cyanate of metal M are mixed and ball-milled, and then heat-treated to obtain the solid electrolyte, which includes:
[0063] S11, mixing lithium hydroxide, a halide of metal M, a cyanate of metal M and a dispersion medium and ball-milling to obtain a ball-milled mixture; during the ball-milling process, the lithium hydroxide, the halide of metal M and the cyanate of metal M undergo an amorphization reaction to generate a precursor, and the ball-milled mixture includes the precursor and the dispersion medium;
[0064] S12, performing separation treatment on the ball-milled mixture to obtain a separated precursor;
[0065] S13, heat-treating the separated precursor to obtain the solid electrolyte.
[0066] That is, a dispersing medium is added to the mixed raw materials to improve the dispersibility of each raw material, improve the reaction effectiveness, reaction uniformity and reaction stability of the amorphization reaction, which is beneficial to improve the amorphous crystal structure accuracy of the precursor and solid electrolyte, and then synergistically improve the ionic conductivity and soft properties of the solid electrolyte.
[0067] Specifically, in some optional embodiments, the dispersion medium includes one or more of hydrocarbons and benzene-based organic liquids that do not contain unsaturated carbon chains, has good dispersibility, and does not react with raw materials, which is beneficial to improving the purity and accuracy of the prepared solid electrolyte.
[0068] Specifically, the mass ratio of the mixed raw material including lithium hydroxide, the halide of metal M, and the cyanate of metal M to the dispersion medium is 1:1 to 1:50; it can be understood that the mass ratio of the mixed raw material to the dispersion medium can be any point value between 1:1 and 1:50; illustratively, the mass ratio of the mixed raw material to the dispersion medium can be 1:0, 1:1, 1:5, 1:10, 1:20, 1:40, 1:50, etc.; in this way, the dispersibility of the mixed raw material can be effectively improved, and the uniformity of the solid electrolyte can be improved. After that, the dispersion medium and the ball milling medium are removed by separation treatment, and the purity of the solid electrolyte will not be affected, so that the ionic conductivity and soft properties of the solid electrolyte are synergistically improved; in some preferred embodiments, the mass ratio of the mixed raw material to the dispersion medium is 1:0 to 1:5.
[0069] Specifically, the temperature of the heat treatment is 50°C to 80°C, and the time is 0.5h to 3h; it can be understood that the temperature of the heat treatment can be any point value between 50°C and 80°C, and the time can be any point value between 0.5h and 3h; illustratively, the temperature of the heat treatment can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., and the time can be 0.5h, 1h, 1.25h, 1.5h, 2h, 2.5h, 3h, etc.; in this way, by-products such as gaseous HCl and HOCN can be effectively removed, and the by-products can be prevented from absorbing moisture and causing adverse effects on the ionic conductivity of the solid electrolyte and the battery performance, thereby improving the overall preparation yield.
[0070] In some preferred embodiments, the heat treatment is performed in a vacuum environment to improve the preparation yield and preparation reliability, which is beneficial to improving the purity of the solid electrolyte.
[0071] The specific embodiments of the present invention are described below in conjunction with the above-mentioned preparation method.
[0072] Example 1
[0073] In the solid electrolyte of this embodiment, y=0.5, M=Ta, X=Cl, a=2, b=2, and the solid electrolyte is prepared by the following steps:
[0074] Lithium hydroxide (LiOH), metal Ta halide (TaCl5) and metal Ta cyanate (Ta(OCN)5) are mixed in a molar ratio of 1:0.5:0.5 to obtain a mixed raw material, and the mixed raw material is mixed with zirconium dioxide ball milling balls in a mass ratio of 1:10 and placed in a 2L zirconium dioxide ball milling jar, and ball milled at a rotation speed of 400 rpm for 30 hours to induce an amorphization reaction to obtain an amorphous precursor.
[0075] The precursor and the zirconium dioxide ball milling balls in the ball milling jar are separated into a dispersion medium and ball milling balls by a sieve to obtain a separated precursor.
[0076] The separated precursor was subjected to vacuum heat treatment at 60°C for 2 h to remove the residual gaseous HCl and HOCN between the material particles to obtain the solid electrolyte LiTaO(OCN)2Cl2. The XRD diffraction pattern of the obtained solid electrolyte LiTaO(OCN)2Cl2 is as follows: Figure 4 shown.
[0077] Example 2
[0078] The difference between this embodiment and the first embodiment is that y=0.75; the rest is the same as the first embodiment.
[0079] Example 3
[0080] The difference between this embodiment and the first embodiment is that y=1.0; the rest is the same as the first embodiment.
[0081] Example 4
[0082] The difference between this embodiment and the first embodiment is that a=1, b=3; the rest is the same as the first embodiment.
[0083] Example 5
[0084] The difference between this embodiment and the first embodiment is that a=0, b=4; the rest is the same as the first embodiment.
[0085] Example 6
[0086] The difference between this embodiment and embodiment 1 is that a=3, b=1; the rest is the same as embodiment 1.
[0087] Example 7
[0088] The difference between this embodiment and embodiment 1 is that M=Hf, a=1.5, b=1.5, and in the process of mixed ball milling, lithium hydroxide (LiOH), metal Hf halide (HfCl4) and metal Hf cyanate (Hf(OCN)4) are used as raw materials to prepare the solid electrolyte LiHfO(OCN) 1.5 Cl 1.5 The XRD diffraction pattern of Figure 5 As shown; the rest is the same as Example 1.
[0089] Example 8
[0090] The difference between this embodiment and embodiment 1 is that M=Nb, and the XRD diffraction pattern of the prepared solid electrolyte LiNbO(OCN)2Cl2 is as follows Figure 6 As shown; the rest is the same as Example 1.
[0091] Example 9
[0092] The difference between this embodiment and embodiment 1 is that X=Br, and the XRD diffraction pattern of the prepared solid electrolyte LiTaO(OCN)2Br2 is as follows Figure 7 As shown; the rest is the same as Example 1.
[0093] Example 10
[0094] The difference between this embodiment and embodiment 1 is that, in the process of mixing and ball milling, anhydrous n-heptane is used as the dispersion medium, and the mass ratio between the mass of anhydrous n-heptane and the total mass of the mixed raw materials is 1:1; the rest is the same as embodiment 1.
[0095] Comparative Example 1
[0096] The difference between this comparative example and Example 1 is that a=4, b=0; the rest is the same as Example 1.
[0097] Comparative Example 2
[0098] The difference between this comparative example and Example 1 is that no heat treatment is performed after the mixing ball milling process; the rest is the same as Example 1.
[0099] Comparative Example 3
[0100] The difference between this comparative example and Example 1 is that the heat treatment is carried out in a vacuum environment at 300°C for 2h, and the XRD diffraction pattern of the obtained solid electrolyte LiTaO(OCN)2Cl2 is as follows Figure 8 As shown; the rest is the same as Example 1.
[0101] Comparative Example 4
[0102] The difference between this comparative example and Example 1 is that y=0.25; the rest is the same as Example 1.
[0103] At least part of the solid electrolytes in the above embodiments and comparative examples were tested respectively, and the testing methods included XRD testing, conductivity testing, Young's modulus testing and all-solid-state battery testing. The test results are shown in Table 1 below.
[0104] The XRD test was conducted in an argon atmosphere with Cu Kα rays as the X-ray source, and an X-ray diffraction device was used to measure the X-ray diffraction patterns of the solid electrolytes of some embodiments and comparative examples.
[0105] The conductivity test is carried out in an argon atmosphere, wherein the powders of the solid electrolytes of some embodiments and comparative examples are filled inside a pressurized mold; inside the pressurized mold, a pressure of 500 MPa is applied to the powder of the solid electrolyte using upper and lower punches; while maintaining the applied pressure, the upper and lower parts of the punches are respectively connected to a potentiostat equipped with a frequency response analyzer, and the ionic conductivity of the solid electrolyte material is measured by an electrochemical impedance spectroscopy; the real value of the impedance at the measuring point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte to ionic conduction.
[0106] The Young's modulus test uses ultrasonic late echo technology to measure the elastic modulus of the sample, using a 5MHz frequency transducer; for an isotropic solid medium, its longitudinal wave velocity CL and transverse wave velocity CS are determined by the density, elastic modulus and Poisson's ratio of the medium. By accurately measuring the longitudinal and transverse wave velocities of the medium, the elastic modulus of the medium can be calculated.
[0107] The all-solid-state battery test was conducted by mixing yLi2O2·MX in a 30:70 mass ratio in an agate mortar in an argon atmosphere. a (OCN) b and positive electrode active material LiCoO2 to obtain a positive electrode mixture; yLi2O2·MX a (OCN) b (60 mg) and Li6PS5Cl solid electrolyte (24 mg) to obtain a first stack; a pressure of 160 MPa is applied to the first stack to form a composite solid electrolyte layer; then, a positive electrode mixture (5 mg) is stacked on the composite solid electrolyte layer to obtain a second stack; a pressure of 360 MPa is applied to the second stack to form a positive electrode layer; then, a metal Li foil (thickness of 300 μm) is stacked on the solid electrolyte layer formed by Li6PS5Cl to obtain a third stack; a pressure of 5 MPa is applied to the third stack to form a negative electrode layer; a collector formed by stainless steel is arranged on the positive electrode layer and the negative electrode layer, and a collector lead is installed on the collector; finally, an insulating hoop is used to isolate the inside of the insulating tube from the external atmosphere, and the inside of the tube is sealed to obtain the following Figure 1 The all-solid-state battery shown; the all-solid-state battery was subjected to 0.1C to 1C electrochemical performance test in the voltage range of 2.5V to 4.2V.
[0108] Table 1 Physical property test results of the embodiments and comparative examples and all-solid-state battery cycle performance test results
[0109]
[0110] Comparing the test data of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 4 in Table 1, it can be seen that the value of y has an important influence on yLi2O2·MX a (OCN) b The conductivity of + The reduction of vacancies or Li + When y is in excess, the physical properties of the solid electrolyte are significantly changed, and the ionic conductivity decreases significantly; when y is in the range of 0.5 to 0.75, the ionic conductivity of the solid electrolyte is within an acceptable range and is at a relatively high level.
[0111] Comparing the test data of Example 1 and Example 4, and Example 5 and Example 6 in Table 1, it can be seen that with the increase of OCN - To Cl - The conductivity changes positively with the increase of the substitution amount; on the one hand, OCN - The ionic radius (197 pm) and I - The ionic radius (181 pm) is close to that of I- The ionic radius and surface charge distribution density are lower, making yLi2O2·MX a (OCN) b The effective ion potential ratio of the system increases; on the other hand, increasing O 2- Content makes the connection [MXO] - Unit and adjacent [MXO] - The polarizability of the bridging oxygen of the unit increases, the charge is further delocalized, and the linear structure of OCN - The incorporation of short-range lattices can relatively improve the room-temperature ionic conductivity of amorphous halide electrolytes.
[0112] As can be seen from Example 7, the high-speed ball milling is used to dope OCN - Replace Cl - The preparation method is also applicable to yLi2O2·MX a (OCN) b , M=Hf amorphous solid electrolyte.
[0113] As can be seen from Example 8, the high-speed ball milling is used to dope OCN - Replace Cl - The preparation method is also applicable to yLi2O2·MX a (OCN) b , a microcrystalline solid electrolyte with M=Nb.
[0114] As can be seen from Example 9, the high-speed ball milling is used to dope OCN - Replace Cl - The preparation method is also applicable to yLi2O2·MX a (OCN) b , an amorphous solid electrolyte with X=Br-.
[0115] As can be seen from Example 10, the high-speed ball milling is used to dope OCN - Replace Cl - In the preparation method of , anhydrous n-heptane is added as a dispersion medium, which is also applicable to yLi2O2·MX a (OCN) b , M=Hf amorphous solid electrolyte.
[0116] In Comparative Example 2, no heat treatment was performed, so HCl and HOCN may absorb moisture, and the obtained solid electrolyte has high ionic conductivity but poor battery performance, and the rate performance cannot be measured; the possible reason is that the ionic conductivity obtained by EIS test contains H + conductivity, and H + Leading to Cl -ionization, thereby corroding the positive electrode layered oxide; by comparing Example 1 with Comparative Example 2, it can be seen that rapid transfer after ball milling and medium and low temperature heat treatment under vacuum are the most effective methods for preparing high-performance yLi2O2·MX a (OCN) b Solid electrolytes are an indispensable requirement.
[0117] In comparative example 3, the amorphous yLi2O2·MX a (OCN) b The heat treatment temperature to the crystallization can improve the ionic conductivity, but it cannot take into account the low modulus at the same time; it can be seen that medium and low temperature heat treatment is the key to maintain high performance yLi2O2·MX a (OCN) b Solid electrolytes are soft and are an essential condition for improving ionic conductivity.
[0118] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A solid electrolyte, characterized in that: The solid electrolyte includes yLi2O2·MX a (OCN) b , wherein 0.5≤y≤1, 0≤a<4, 0<b≤4, a+b=3 or 4, X is at least one of Cl and Br, and M is at least one of Ta, Hf and Nb.
2. The solid electrolyte according to claim 1, characterized in that 0.5≤y≤0.75。 3. The solid electrolyte according to claim 1, characterized in that The crystal structure of the solid electrolyte is at least one of an amorphous state and a microcrystalline state.
4. The solid electrolyte according to claim 1, characterized in that The Young's modulus of the solid electrolyte is less than or equal to a preset Young's modulus, and the preset Young's modulus is 7 Gpa to 10 Gpa; The ionic conductivity of the solid electrolyte is greater than or equal to a preset conductivity, and the preset conductivity is 5 mS / cm to 7 mS / cm.
5. The solid electrolyte according to any one of claims 1 to 4, characterized in that The solid electrolyte also includes Li3YCl6, Li3InCl6, Li2S·P2S5, Li2S·P2S5·LiI, Li2S·P2S5·LiCl, Li2S·P2S5·LiBr, Li2S·P2S5·Li2O, Li2S·P2S5·Li2O·LiI, Li2S·SiS2, Li2S·SiS2·LiI, Li2S·SiS2·LiBr, Li2S·SiS2·LiCl, Li2S·SiS2·B2S3·LiI, Li2S·SiS2·P2S5·LiI, Li2S·B2S3, Li2S·P2S5·Z m S n , Li2S·GeS2, Li2S·SiS2·Li3PO4, Li2S·SiS2·Li c NO d and Li 10 GeP2S 12 At least one of; Wherein, m and n are positive numbers, Z is one of Ge, Zn and Ga; c and d are positive numbers, and N is one of P, Si, Ge, B, Al, Ga and In.
6. The solid electrolyte according to any one of claims 1 to 4, characterized in that The solid electrolyte is used in an all-solid-state battery, which includes a positive electrode layer, a negative electrode layer and a separation layer, wherein the separation layer is located between the positive electrode layer and the negative electrode layer, and at least one of the positive electrode layer, the negative electrode layer and the separation layer includes the solid electrolyte.
7. An all-solid-state battery, characterized in that: Comprising the solid electrolyte according to any one of claims 1 to 6.
8. A method for preparing a solid electrolyte, characterized in that: include: The solid electrolyte is obtained by mixing lithium hydroxide, a halide of metal M and a cyanate of metal M with a ball mill and performing a heat treatment. The solid electrolyte includes yLi2O2·MX a (OCN) b , wherein 0.5≤y≤1, 0≤a<4, 0<b≤4, a+b=3 or 4, X is at least one of Cl and Br, and M is at least one of Ta, Hf and Nb.
9. The method for preparing a solid electrolyte according to claim 8, characterized in that: The temperature of the heat treatment is 50° C. to 80° C., and the time is 0.5 h to 3 h.
10. The method for preparing a solid electrolyte according to claim 8, characterized in that: The solid electrolyte is obtained by mixing lithium hydroxide, a halide of metal M and a cyanate of metal M with ball milling and heat treating, and comprising: The lithium hydroxide, the halide of the metal M, the cyanate of the metal M and the dispersion medium are mixed and ball-milled to obtain a ball-milled mixture; during the ball-milling process, the lithium hydroxide, the halide of the metal M and the cyanate of the metal M undergo an amorphization reaction to generate a precursor, and the ball-milled mixture includes the precursor and the dispersion medium; performing separation treatment on the ball-milled mixture to obtain a separated precursor; The separated precursor is heat treated to obtain the solid electrolyte.